2015
DOI: 10.1016/j.spinee.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intact glycosaminoglycans from intervertebral disc-derived notochordal cell-conditioned media inhibit neurite growth while maintaining neuronal cell viability

Abstract: BACKGROUND CONTEXT Painful human intervertebral discs (IVDs) exhibit nerve growth deep into the IVD. Current treatments for discogenic back pain do not address the underlying mechanisms propagating pain and are often highly invasive or only offer temporary symptom relief. The notochord produces factors during development that pattern the spine and inhibit growth of dorsal root ganglia (DRG) axons into the IVD. We hypothesize that notochordal cell (NC) conditioned medium (NCCM) includes soluble factors capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 46 publications
1
50
3
2
Order By: Relevance
“…We observed that NCCM could inhibit endothelial cell invasion and tubular formation in the presence of TNFα confirming the anti-inflammatory effects of NC derived factors and their ability to function in the presence of TNFα which stimulated production of multiple pro-inflammatory cytokines, many of which have been detected in the degenerate human IVD 16 . Our previous work has shown that NCCM inhibits neurite outgrowth from both neuroblastoma and DRG cells whilst maintaining cell viability and that CS is a factor in NCCM responsible for these inhibitory effects 30 . Together, these results demonstrate that NCCM has both antineuronal and anti-angiogenic potential as well as structure-modifying properties which can be used to target the degenerate and painful IVD 32 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We observed that NCCM could inhibit endothelial cell invasion and tubular formation in the presence of TNFα confirming the anti-inflammatory effects of NC derived factors and their ability to function in the presence of TNFα which stimulated production of multiple pro-inflammatory cytokines, many of which have been detected in the degenerate human IVD 16 . Our previous work has shown that NCCM inhibits neurite outgrowth from both neuroblastoma and DRG cells whilst maintaining cell viability and that CS is a factor in NCCM responsible for these inhibitory effects 30 . Together, these results demonstrate that NCCM has both antineuronal and anti-angiogenic potential as well as structure-modifying properties which can be used to target the degenerate and painful IVD 32 .…”
Section: Discussionmentioning
confidence: 98%
“…For blocking studies, NCCM and basal medium ( n = 4) were treated with 0.05 U/ml Chondroitinase ABC (Chon-ABC) (Sigma #C3667) at 37°C for 30 min to digest CS and dermatan sulfate (DS). Our previous work has shown that CS forms the major glycosaminoglycan (GAG) in NCCM 30 . HUVECs were then treated with: (1) Basal medium, (2) Basal medium with Chon-ABC, (3) NCCM (100%), and (4) NCCM (100%) with Chon-ABC, for both the cell invasion and tubular formation assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An optimized decellularization process for nucleus pulposus needs to balance the removal of cells with the maintenance of sGAGs. The sGAGs are essential in maintaining the osmotic pressure of the nucleus pulposus [8], and they have the potential to play a role in driving cell phenotype [45][46][47]50,58] and preventing innervation [59][60][61][62]. The gentle decellularization protocol used in our laboratory for nerve [39,43,63] and lung tissue [38] was adapted for use in the nucleus pulposus by shortening the duration of wash cycles substantially.…”
Section: Discussionmentioning
confidence: 99%
“…2015, Purmessur et al. 2015). The progressive change in the ECM of the NP ultimately leads to the loss of the biomechanical functions of IVDs that is associated with increasing age.…”
Section: Intervertebral Discsmentioning
confidence: 99%